If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2m + -2 = 9m + 34 + -3m Reorder the terms: 4 + -2 + 2m = 9m + 34 + -3m Combine like terms: 4 + -2 = 2 2 + 2m = 9m + 34 + -3m Reorder the terms: 2 + 2m = 34 + 9m + -3m Combine like terms: 9m + -3m = 6m 2 + 2m = 34 + 6m Solving 2 + 2m = 34 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 2 + 2m + -6m = 34 + 6m + -6m Combine like terms: 2m + -6m = -4m 2 + -4m = 34 + 6m + -6m Combine like terms: 6m + -6m = 0 2 + -4m = 34 + 0 2 + -4m = 34 Add '-2' to each side of the equation. 2 + -2 + -4m = 34 + -2 Combine like terms: 2 + -2 = 0 0 + -4m = 34 + -2 -4m = 34 + -2 Combine like terms: 34 + -2 = 32 -4m = 32 Divide each side by '-4'. m = -8 Simplifying m = -8
| (-4.9)(7.2)= | | 1.2p-3.6=0.6p-6.4-2.6p | | (x^2-5x)(2x^2+x-3)=equation | | (1/4)+(2/x)=(11/4x) | | 1/3c-(-5)=11 | | y^2-14y=-26 | | y+10=-4 | | 3+n/4=-11 | | 5x-6=2(3x-1)-x | | 2x=(x+11)2 | | -5x-4(x-6)=12 | | (x)+3=5 | | (2x^2-4x)(6x^2-5x)=equation | | k/9=67 | | -2m=5m+68 | | 10p*79l=36666 | | 6m+7m=52 | | -5/9+x=3/4 | | 34j=56 | | x/12=-6 | | (x^2+2x+1)(x^2+4x+4)=equation | | (x^3+4x^2+5x+2)(x+2)=equation | | 3*(1-x)-5*(x+2)=1-4x | | 4(x-3)+3ax=5x-9 | | 6t+5=7t-3 | | 7.3=a/5+1/2 | | -6(3b+4)+(19b-9)=0 | | 10=a/-4 | | 2*(2+x)+3*(4x-1)=10x-7 | | 2a^2-3=0 | | 3x^2-17x=-2x^2-5x-4 | | 3.6q-5.7-2.8q=-0.2q-1.5 |